General design flow for waveguide Bragg gratings - Brückerhoff-Plückelmann, Frank; Buskasper, Tim; Römer, Julius; Krämer, Linus; Malik, Bilal; McRae, Liam; Kürpick, Linus; Palitza, Simon; Schuck, Carsten; Pernice, Wolfram (Nanophotonics, 2025)
Bragg gratings are crucial components in passive photonic signal processing, with wide-ranging applications including biosensing, pulse compression, photonic computing, and addressing. However, the design of integrated waveguide Bragg gratings (WBGs) for arbitrary wavelengths presents significant challenges, especially when dealing with highly asymmetric layer stacks and large refractive index contrasts. Convenient approximations used for fiber Bragg gratings generally break down in these cases, resulting in nontrivial design challenges. In this work, we introduce a general simulation and design framework for WBGs, which combines coupled mode theory with three-dimensional finite-element method eigenfrequency computations. This approach allows for precise design and optimization of WBGs across a broad range of device layer stacks. The design flow is applicable to further layer stacks across nearly all wavelengths of interest, given that the coupling between the forward and backward propagating mode is dominant.